The Orexin/Hypocretin System - Shekhar, Anantha, 1957-; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2012)
This issue of Progress in Brain Research reviews current knowledge and understanding, provides a starting point for researchers and practitioners entering the field, and builds a platform for further research and discovery. Leading authors review the state-of-the-art in their field of investigation, and provide their views and perspectives for future research Chapters are extensively referenced to provide readers with a comprehensive list of resources on the topics covered All chapters include comprehensive background information and are written in a clear form that is also accessible to the non-specialist.
Many faces of orexin/hypocretin / A. Shekhar (IN, USA) -- Overview of orexin/hypocretin system / M. Mieda and T. Sakurai (Ishikawa, Japan) -- Hypocretins and the neurobiology of sleep-wake mechanisms / L. de Lecca (CA, USA) -- Respiration and autonomic regulation and orexin / E. Nattie and A. Li (NH, USA) -- Orexins, feeding, and energy balance / E. Girault, C.-X. Yi, E. Fliers and A. Kalsbeek (Amsterdam, The Netherlands and OH, USA) -- Orexin and natural reward: Feeding, maternal, and male sexual behavior / A.R. Di Sebastiano and L.M. Coolen (MI, USA and Ontario, Canada) -- Multiple roles for orexin/hypocretin in addiction / S.V. Mahler, R.J. Smith, D.E. Moorman, G.C. Sartor and G. Aston-Jones (SC, USA) -- Hypocretin modulation of drug-induced synaptic plasticity / C. Baimel and S.L. Borgland (BC, Canada).
Text in English.
Includes bibliographical references and index.
Online resource; title from HTML table of contents page (ScienceDirect, viewed May 25, 2018).
Elsevier
Keywords: Orexins; Narcolepsy; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Narcolepsy; Orexins; Neuropeptides; Narcolepsy; Receptors, Neuropeptide; Electronic books